2018
DOI: 10.1016/j.soilbio.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Harmful or useful? A case study of the exotic peregrine earthworm morphospecies Pontoscolex corethrurus

Abstract: A B S T R A C TExotic peregrine earthworms are often considered to cause environmental harm and to have a negative impact on native species, but, as ecosystem engineers, they enhance soil physical properties. Pontoscolex corethrurus is by far the most studied morphospecies and is also the most widespread in tropical areas. The term of morphospecies is used in this review because P. corethrurus may in fact constitute a complex of cryptic species. This earthworm is found in a wide range of habitats, from apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 128 publications
(177 reference statements)
2
42
0
Order By: Relevance
“…This positive priming effect is expected to promote the recycling of nutrients, especially of organic N and P, in the SOM (Kuzyakov et al, 2000;Bertrand et al, 2015). This has been shown for P. corethrurus in several studies, summarised in the recent review by Taheri et al (2018). FIGURE 4 | Relative abundance of microbial phyla reported in soils or substrates processed by earthworms of different functional groups.…”
Section: Earthworms Increase Nutrient Mineralisation In the Soilmentioning
confidence: 81%
“…This positive priming effect is expected to promote the recycling of nutrients, especially of organic N and P, in the SOM (Kuzyakov et al, 2000;Bertrand et al, 2015). This has been shown for P. corethrurus in several studies, summarised in the recent review by Taheri et al (2018). FIGURE 4 | Relative abundance of microbial phyla reported in soils or substrates processed by earthworms of different functional groups.…”
Section: Earthworms Increase Nutrient Mineralisation In the Soilmentioning
confidence: 81%
“…Hureta et al [49] also observed that this species prefers soil with high silt content while Marichal et al [50] observed positive relationship between clay content and P. corethrurus. The P. corethrurus were found in high density in a sandy soil having low organic matter content [29]. High abundance of this species in sandy soil may be due to assimilation of carbon released in the soil from plant roots [51].…”
Section: Resultsmentioning
confidence: 98%
“…Total 24 earthworms individual were collected from sampling site, out which only 6 earthworms were P. corethrurus while others earthworms belongs to species Metaphire posthuma and Amynthas morissi. The coexistence of this species with other native species had been observed in several sites of Brazil, India, Thailand and Singapore [28,29]. Dash and Saxena [30] Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The glossoscolecid earthworm Pontoscolex corethrurus (six samples, one with two repeats) is a species complex with a circum‐tropical distribution, native to South and Central America, but introduced in tropical and subtropical regions worldwide (Taheri et al . ). The family has no relatives in temperate environments and the genetic distance to other clitellate families rules out misidentification due to amplification or sequencing errors.…”
Section: Discussionmentioning
confidence: 97%